A House of Night: Destined - Book 9 - Cast, P. C.; Cast, Kristin (New York : St. Martin's Griffin, 2011)
Zoey is home where she belongs, safe with her Guardian Warrior, Stark, by her side; Kalona has released his hold on Rephaim; and through Nyx's gift of a human form, he and Stevie Rae are finally able to be together.
Keywords: Redbird, Zoey (Fictional character) -- Fiction; Teenagers -- Fiction; Vampires -- Fiction; Fiction; Fiction